2022
DOI: 10.1111/ajr.12899
|View full text |Cite
|
Sign up to set email alerts
|

Nursing in a different world: Remote area nursing as a specialist–generalist practice area

Abstract: Objective: Remote area nurses provide primary health care services to isolated communities across Australia. They manage acute health issues, chronic illness, health promotion and emergency responses. This article discusses why their generalist scope of practice should be formally recognised as a specialist nursing practice area.Design: Constructivist grounded theory, using telephone interviews (n = 24) with registered nurses and nurse practitioners.Setting: Primary health care clinics, in communities of 150-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 33 publications
(66 reference statements)
0
27
0
Order By: Relevance
“…They are often required to work in diverse cultural and geographical contexts, responding to emergencies and a wide range of acute and chronic health conditions in isolation, or with the local health care workers including Aboriginal Health Practitioners and nonclinical staff to support the people they care for. 6,7 To practice in rural and remote Australia, RNs are required to be multiskilled and practice as an extended generalist when delivering primary health care. 7,8 Therefore, it is important that RNs have the core capabilities and clinical skills to provide care to rural and remote Australians.…”
Section: E D I T O R I a L F R O M T H E A L L I A N C Ementioning
confidence: 99%
See 1 more Smart Citation
“…They are often required to work in diverse cultural and geographical contexts, responding to emergencies and a wide range of acute and chronic health conditions in isolation, or with the local health care workers including Aboriginal Health Practitioners and nonclinical staff to support the people they care for. 6,7 To practice in rural and remote Australia, RNs are required to be multiskilled and practice as an extended generalist when delivering primary health care. 7,8 Therefore, it is important that RNs have the core capabilities and clinical skills to provide care to rural and remote Australians.…”
Section: E D I T O R I a L F R O M T H E A L L I A N C Ementioning
confidence: 99%
“…Furthermore, registered nurses (RNs) are often the first point of call for patient consultations where there are no other health professionals available such as general practitioners. They are often required to work in diverse cultural and geographical contexts, responding to emergencies and a wide range of acute and chronic health conditions in isolation, or with the local health care workers including Aboriginal Health Practitioners and nonclinical staff to support the people they care for 6,7 …”
mentioning
confidence: 99%
“…24,25 Furthermore, the development of skills and knowledge in generalist settings may assist in overcoming issues related to working in a resource-poor environment. 7 It has been suggested that to assist RANs to work within their scope, support and supervision are required when transitioning from an acute care setting to the remote health setting. 7 Clinical supervision aims to improve quality, safety and challenge standards of care 26 and is not considered performance management or managers providing direction.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…7 It has been suggested that to assist RANs to work within their scope, support and supervision are required when transitioning from an acute care setting to the remote health setting. 7 Clinical supervision aims to improve quality, safety and challenge standards of care 26 and is not considered performance management or managers providing direction. 27 'Mentoring' and 'preceptorship' are often used interchangeably for 'clinical supervision' in rural and remote nursing practice.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation